169 EFFECTS OF ESTROGEN AND AGING ON INTRACELLULAR O-GLYCOSYLATION (O-GlcNAc) IN THE VASCULATURE. (1st January 2006) - Xing, D.; Oparil, S.; Chen, Y. -F.; Feng, W.; Kudlow, J. E.; Miller, A. P.
Abstract : Background: O-GlcNAc is a dynamic post-translational modification of many nuclear and cytoplasmic proteins. Blocking or reducing O-GlcNAc renders cells more sensitive to stress and decreases their survival, while increasing O-GlcNAc levels protects cells. We have shown that 17b-estradiol (E2) has vasoprotective and anti-inflammatory effects after acute arterial injury in young but not in aged rats. This study tested whether O-GlcNAc modification could be related to our age-dependent findings and whether it plays a role in E2-mediated vascular responses in young animals. Methods: Intact young (2 mo old) and aged (18 mo old) female Sprague-Dawley rats were euthanized. Carotid arteries were excised, fixed, embedded, and evaluated by immunofluoresence with the selective mouse monoclonal anti-O-GlcNAc antibody (RL2). Aortic smooth muscle cells (ASMCs) were isolated from rats of the same age, passaged (# 3), made quiescent, and then treated with E2 (0.1 μM) or vehicle for 24 hrs. Immunofluorescence staining of ASMCs and Western blot analysis was performed with RL2. Results: O-glycosylated protein levels in the media of carotid arteries were lower in aged compared to young rats. Similarly, O-glycosylated protein levels were lower and less concentrated in nuclei of ASMCs from aged compared to young rats. E2 treatment significantly increased O-glycosylated protein levels in young but not in aged ASMCs (Figure 7). Western analysis demonstrated E2-induced increases in global O-glycosylated protein levels only in ASMCs from young rats (Figure 8). Conclusions: Global O-glycosylated protein levels are lower in aged compared to young rat carotid arteries. E2 up-regulates O-GlcNAc in young but not in aged rat ASMCs. O-GlcNAc may play an important role in E2-induced vasoprotection and its age-related modification.